Precise tuning of disulphide crosslinking in mRNA polyplex micelles for optimising extracellular and intracellular nuclease tolerability. (3rd July 2019) - Dirisala, Anjaneyulu; Uchida, Satoshi; Tockary, Theofilus A.; Yoshinaga, Naoto; Li, Junjie; Osawa, Shigehito; Gorantla, Lahari; Fukushima, Shigeto; Osada, Kensuke; Kataoka, Kazunori
Abstract: The major issues in messenger (m)RNA delivery are rapid mRNA degradation in the extracellular and intracellular spaces, which decreases the efficiency and duration for protein expression from mRNA. Stabilization of mRNA carriers using environment-responsive crosslinkings has promises to overcome these issues. Herein, we fine-tuned the structure of disulphide crosslinkings, which are selectively cleaved in the intracellular reductive environment, using the mRNA-loaded polyplex micelles (PMs) prepared from poly(ethylene glycol)–poly(L-lysine) (PEG–PLys) block copolymers, particularly by focussing on cationic charge density after the crosslinking. Primary amino groups in PLys segment were partially thiolated in two ways: One is to introduce 3-mercaptopropionyl (MP) groups via amide linkage, resulting in the decreased cationic charge density [PEG–PLys(MP)], and the other is the conversion of amino groups to 1-amidine-3-mercaptopropyl (AMP) groups with preserving cationic charge density [PEG–PLys(AMP)]. Compared to non-crosslinked and PEG–PLys(MP) PMs, PEG–PLys(AMP) PM attained tighter mRNA packaging in the PM core, thereby improving mRNA nuclease tolerability in serum and intracellular spaces, and providing enhanced protein expression in cultured cells at the optimal crosslinking density. These findings highlight the importance of cationic charge preservation in installing crosslinking moieties, providing a rationale for mRNA carrier design in the molecular level.